Acute monoplegia secondary to herpes zoster infection: a case report - Kasapoglu Aksoy, Meliha; Altan, Lale; Solum, Sezin (The European Research Journal, 2017)
Brachial plexopathy with motor involvement secondary to herpes zoster infection is very rare. Also known as shingles, herpes zoster occurs as a result of reactivation of varicella zoster virus in the dorsal root ganglia. We present a 69-year-old male patient with right upper extremity monoplegia secondary to herpes zoster infection. Physical examination showed scars from rash on his right antecubital fossa. Electroneuromyography showed a low amplitude motor response of the right median nerve, while having no sensation response at digits 1 and 3. Right ulnar and radial nerve sensation responses were lower in amplitude compared to the left side. Herpes zoster should be considered in the differential diagnosis of acute monoparesis. It is very important in avoiding unnecessary tests and treatments.